2014
DOI: 10.1038/ejhg.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent triplication and uniparental isodisomy: evidence for microhomology-mediated break-induced replication model for genomic rearrangements

Abstract: Whole-genome oligonucleotide single-nucleotide polymorphism (oligo-SNP) arrays enable simultaneous interrogation of copy number variations (CNVs), copy neutral regions of homozygosity (ROH) and uniparental disomy (UPD). Structural variation in the human genome contributes significantly to genetic variation, and often has deleterious effects leading to disease causation. Co-occurrence of CNV and regions of allelic homozygosity in tandem involving the same chromosomal arm are extremely rare. Replication-based me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…The emerging picture is a perplexing fractal: large genomic-scale structural variants, that is, alterations involving megabases of DNA, can be associated with additional complexities, such as other structural variants that are generated in a one-off event (chromoanasynthesis and chromothripsis-like events (FIG. 5a)) 8,9 or a CGR accompanied by AOH 11,12 . Further alterations might be revealed when these structural variants are scrutinized down to the base-pair sequence level owing to the presence of small-scale changes that can act as mutational signatures, for example, insertions or deletions of short DNA segments and/or de novo point mutations that are present adjacent to the junction of a structural variant 10,106,128,143 (FIG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging picture is a perplexing fractal: large genomic-scale structural variants, that is, alterations involving megabases of DNA, can be associated with additional complexities, such as other structural variants that are generated in a one-off event (chromoanasynthesis and chromothripsis-like events (FIG. 5a)) 8,9 or a CGR accompanied by AOH 11,12 . Further alterations might be revealed when these structural variants are scrutinized down to the base-pair sequence level owing to the presence of small-scale changes that can act as mutational signatures, for example, insertions or deletions of short DNA segments and/or de novo point mutations that are present adjacent to the junction of a structural variant 10,106,128,143 (FIG.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CNVs and SNVs can be generated concomitantly 10 , and SNVs created during mutagenic repair can potentially affect the function of genes that do not map within the CNV. Also, CNVs can be followed by extended regions of absence of heterozygosity (AOH) 11,12 . If the AOH that is generated from template switching between homologues versus sister chromatids occurs at an imprinted locus, disease can result.…”
mentioning
confidence: 99%
“…Occurrence of complex genomic rearrangements (CGRs) associated with an extended segment of UPD has been recently reported, [7][8][9] but the underlying molecular mechanism has remained elusive. We speculate that the previous lack of such CGR þ AOH observations is due to the absence of genomic visualization of such potential events prior to the recent introduction of high-resolution microarrays with genome-wide coverage and the capacity to resolve CNVs and genotype SNPs in the same experimental assay.…”
Section: Introductionmentioning
confidence: 99%
“…The main steps of this model include invasion of a single segment of the broken double strand in a sister chromatid replication fork or a homologous chromosome chromatid. The invasion and hybridization in the homologous chromosome, instead of the sister chromatid, may result in LOH [Sahoo et al, 2015]. Many deletion cases associated with extensive LOH were reported in cells of patients with acute lymphoblastic leukemia [Mullighan et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Many deletion cases associated with extensive LOH were reported in cells of patients with acute lymphoblastic leukemia [Mullighan et al, 2007]. Sahoo et al [2015] identified and characterized 2 cases of interstitial triplication followed by LOH, the first detailed genomic analysis providing support for an MMBIR mechanism, inducing gains in copy number with tandem uniparental isodisomy. Zhang et al [2009] also proposed that the DNA FoSTeS/MMBIR replication mechanism is capable of producing complex rearrangements.…”
Section: Discussionmentioning
confidence: 99%